Eurozone governance and the German demand and growth regimes, 1999-2024 - Juan Manuel Campana; Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
This paper provides a comprehensive analysis of the German demand and growth regimes from 1999 to 2024 within the framework of Eurozone macroeconomic governance for three sub-periods: 1999-2009, 2010-2020, and 2021-2024. Applying a national income and financial accounting decomposition approach, we find an extreme export-led mercantilist (ELM) regime during the first period, a moderated ELM regime in the second period, and a weakly export-led (WEL) regime in the third period. Also, the application of the Sraffian supermultiplier growth accounting approach indicates that exports were the primary autonomous growth driver, though with a declining trend over time. The examination of the structural underpinnings of Germany's export-led regime reveals that exports are mainly in capital goods and medium to high-technology products with a high income elasticity of demand, and thus rely on growth dynamics in the respective destination countries. The analysis of the German macroeconomic policy regime shaped by the Eurozone governance system finds for the first period a restrictive macroeconomic policy stance that suppressed domestic demand, making exports the primary growth driver. The second period saw a more expansionary stance, leading to a less extreme ELM regime. This trend continued into the third period, leading to a WEL regime with balanced domestic and external growth drivers. The paper concludes by advocating for a coordinated Eurozone macroeconomic policy mix that generates sufficient domestic demand and imports to balance the structurally shaped German export dynamics and to prevent regional and global current account imbalances.
Keywords: E11; E12; E61; O52; 330; Eurozone governance; Germany; growth decomposition; macroeconomic policy regime